2009
DOI: 10.1590/s0004-282x2009000500016
|View full text |Cite
|
Sign up to set email alerts
|

Pain in tropical spastic paraparesis/HTLV-I associated myelopathy patients

Abstract: -Objective: Tropical Spastic Paraparesis/HTLV-I Associated Myelopathy (TSP/HAM) is a chronic myelopathy, and pain has been mentioned as a frequent sensory symptom in this condition. The authors aimed at analyzing this symptom in a TSP/HAM patients series. Method: For this, 46 patients were analyzed considering demographic and clinical characteristics and complaint of pain as to verbal description, time of onset and classification, correlated with the degree of motor disability and type of pain. Results: Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Recent experiments are testing the use of topically applied anesthetics before tDCS as to decrease minimal pain and itching associated with the effects of the electrical current, thus to decrease placebo response. 6 In addition, as it has been demonstrated in other chronic low back pain syndromes, 41 supraspinal neuroplastic changes might also take part in chronic pain mechanisms in HTLV-1 infection. Previous studies have shown that a high proportion of these patients have chronic low back and/or lower limbs pain of mixed origin.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Recent experiments are testing the use of topically applied anesthetics before tDCS as to decrease minimal pain and itching associated with the effects of the electrical current, thus to decrease placebo response. 6 In addition, as it has been demonstrated in other chronic low back pain syndromes, 41 supraspinal neuroplastic changes might also take part in chronic pain mechanisms in HTLV-1 infection. Previous studies have shown that a high proportion of these patients have chronic low back and/or lower limbs pain of mixed origin.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, a recent clinical trial showed that blinding effectiveness of tDCS was similar to placebo pills-the gold standard of blinding method. [6][7][8] In general, there is no overall preponderance of neuropathic over nociceptive pain; nevertheless, when superimposed, neuropathic pain characteristics are usually more disabling. Recent experiments are testing the use of topically applied anesthetics before tDCS as to decrease minimal pain and itching associated with the effects of the electrical current, thus to decrease placebo response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HTLV-1-infected CD4 + T lymphocytes of HAM/TSP patients exhibit spontaneous proliferation, in addition to an increased production of proinflammatory cytokines such as IFN-γ, TNF-α, IL-1, and IL-6; neurotoxic cytokines such as IFN-γ and TNF-α, in particular, are found at high concentrations in the spinal fluid of HAM/TSP patients [ 9 , 16 , 50 , 51 ]. These findings demonstrate that infected individuals have an immune response characteristic of the Th1 phenotype (IFN-γ and TNF-α) and a decrease in the Th2 profile (IL-4 and IL-10) [ 30 , 31 , 45 ].…”
Section: Immunological Changes In Htlv-1-infected Patientsmentioning
confidence: 99%